Building History and Architecture of The Ancient Egyptian Pyramids - Mominov Nodirbek; Qalandarova Madina (Peerian Journals Publishing, 2023)
The history of Egyptian ehrams, which have been living for more than four thousand years, their construction system and architecture is the main question that world scientists and world historians have been thinking about. Scientists have different opinions about the reasons for the construction of these Pyramids, which are a unique construction of those times, especially about the different ways of construction and the products used. The diversity of these opinions has been influencing the creation of a consensus. This article also provides extensive information on these topics.
Keywords: Pyramids; Egypt; Ehrams